Requirements for Rice Carbon Credit Projects - Nelson, Katherine (International Rice Research Institute, 2025)
Presented during the 2025 APSA Field Crops Webinar, the presentation discusses the potential for rice cultivation to mitigate greenhouse gas emissions. It highlights that while rice cultivation contributes a smaller percentage to global agricultural emissions than livestock, it has a higher mitigation potential. The presentation also introduces "Alternate Wetting & Drying (AWD)" as a water-saving technology that can reduce methane emissions in rice fields by up to 33% without sacrificing yield. Finally, it outlines the steps involved in setting up a rice carbon credit project, from defining the project's purpose and methodology to training farmers and validating emission reductions.